2010
DOI: 10.3341/kjo.2010.24.5.284
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Parameters Using Pentacam and Prediction of Corneal Endothelial Cell Loss after Cataract Surgery

Abstract: PurposeWe evaluated various preoperative anterior segment parameters measured with a Pentacam rotating Scheimpflug camera and compared them with those of conventional methods. We also evaluated the effect of different parameters on corneal endothelial cells after cataract surgery.MethodsPentacam examination was performed in 88 eyes from 88 patients to evaluate central anterior chamber depth (ACDpentacam), nuclear density (Densitometrypentacam), anterior chamber volume (ACV), and lens thickness (LTpentacam). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
1
25
1
2
Order By: Relevance
“…Another study found a mean LD of 11.95 %±4.06 % with a mean nuclear opacity of 3.07 within the LOCS III classification, comparable to our result of LD. In their study, LD could be identified as a risk factor for predicting percentage change of endothelial cell density, which we did not show in our study [20]. LD only reached a small range from 7.1 to 34.1 % within the study by Cho et al, so they concluded that the clinical opacitiy classification might have been overestimated.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Another study found a mean LD of 11.95 %±4.06 % with a mean nuclear opacity of 3.07 within the LOCS III classification, comparable to our result of LD. In their study, LD could be identified as a risk factor for predicting percentage change of endothelial cell density, which we did not show in our study [20]. LD only reached a small range from 7.1 to 34.1 % within the study by Cho et al, so they concluded that the clinical opacitiy classification might have been overestimated.…”
Section: Discussioncontrasting
confidence: 78%
“…ACV was calculated using integral calculus. In our study, ACV was calculated within the Pentacam software [20].…”
Section: Discussionmentioning
confidence: 99%
“…11,13,32 Corneal densitometry has been assessed, and the degree of subepithelial corneal haze and stromal scarring in refractive surgery patients has been quantified. 9,10,12 Most studies used slitlamp observation and subjective assessment to report haze after keratorefractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The Pentacam (Oculus Optikger€ ate GmbH) is a noninvasive optical system that uses the Scheimpflug principle to take up to 50 cross-sectional images of the entire anterior segment within 2 seconds. 11 The ability to measure changes in corneal transparency noninvasively and objectively may enable more precise monitoring of progression and may improve patient management.…”
mentioning
confidence: 99%
“…Corneal densitometry provides information about corneal clarity and thus an indication of cornea health. Densitometry is expressed in grayscale unit from 0 to 100; 0 means minimum backscattering of light (no clouding) and 100 means maximum backward scattering of light (opaque) [12]. An example of the data output is shown in figure 10.…”
Section: Discussionmentioning
confidence: 99%